Full SiC Version of the EDA5 Inverter - Chowdhury, Shajjad; Gurpinar, Emre; Castellazzi, Alberto (2017)
Recently, a novel hybrid multilevel inverter topology, the EDA5, was presented. The novel inverter topology comprises of two floating capacitors and 16 active switches to achieve five-level output voltage waveform and achieves higher efficiency at low-modulation index compared to a five-level Active Neural Point Clamped (5L-ANPC) converter. In this work, a full SiC MOSFET version of the inverter is presented, using commercially available 1200V rated devices. A balanced mix of simulation and experimental results are presented to point out the salient features of the topology. The topology is compared with 5L-ANPC inverter in simulation, and experimentally demonstrated up to 12kW output power with 1kV DC link voltage.